Farmer's Dilemma: The Pursuit of Profit or Surviving in Dragon Fruit Farming - Meyliani, Lisa; Yuswadi, Hary (Jurnal ENTITAS SOSIOLOGI, 2019)
Dragon fruit farmers in Kedungasri Village, Banyuwangi Regency, have logical rationality in maintaining dragon fruit farming. Farmers assume that this crop is more profitable than other plants such as oranges, melons, watermelons, and others. Dragon fruit is a one-time crop, and farmers can harvest many times. Although like oranges, farmers have to wait one year to be able to collect them. The theory used in this study is the theory of farmers' rationality, according to Popkin (1979). While the research method used is a descriptive qualitative approach. The findings of this study are the dragon fruit farmers have their techniques and strategies to increase profits. Besides, the secret competition also takes place between them to increase fruit productivity and quality. Unfortunately, farmers experience a dilemma in the agricultural business. The dilemma experienced by farmers is weak market access and lack of protection from the state for the market. Farmers also have difficulty getting fertilizers and medicines, and there is no help from the government to improve agriculture. The government paid little attention to the dragon fruit farmers, making farmers have to survive under market pressure. Keywords: dragon fruit farmers, rationality, farmers' dilemma. Referensi: Popkin, S. L. (1979). The Rational Peasant The Political Economy of Rural Society in Vietnam. Berkeley: University of California Press. Scott, J. C. (1981). Moral Ekonomi Petani. Jakarta: LP3ES. Syahyuti. (2014). Mau Ini Apa Itu? "Komparasi Konsep, Teori dan Pendekatan dalam Pembangunan Pertanian dan Pedesaan: (125 versus 125)". Jakarta: Amplitudo Media Science. Yuswadi, H. (2005). Melawan Demi Kesejahteraan: Perlawanan Petani jeruk Terhadap Kebijakan Pembangunan Pertanian. Jember: Kompyawisda JATIM. Yuswadi, H. (2017). Metode Penelitian Sosial Perbandingan Pendekatan Kualitatif dan Kuantitatif. Jember: Universitas Jember.